Development and investigation of lanthanide-doped oxide nanocrystals for nanothermometry - Nogueira, Camila Tsuchida (2024)
Temperature sensing with accuracy and good spectral resolution is highly sought in research and industry, especially in biomedicine and microelectronics, where conventional thermal probes are unsuitable for remote measurements below 10 μm. In biology, thermal monitoring can indicate inflammatory areas, diseases, and tumors. Previous studies suggest temperature monitoring is promising for early diagnosis and assisting disease treatments, such as hyperthermia for cancer treatment. In this regard, luminescent nanoprobes made of inorganic materials doped with rare-earth ions have emerged as an effective means to measure local temperature precisely and remotely. The thermal readout is obtained by tracking the Luminescence Intensity Ratio (LIR) between two photoluminescence (PL) emission lines, which evolves with temperature. A calibration curve between LIR and temperature can then be extracted from experimental data in the laboratory. Nonetheless, developing adequate luminescent nanothermometers for biological applications continues to be a major hurdle. These thermal sensors must be small, stable and well-dispersed in physiological solutions, nontoxic, and exhibit strong PL emissions within the biological windows (BWs) ¾ the wavelength ranges where light penetrates tissues deeply. This work focuses on oxides doped with rare-earth ions for nanothermometry in future biological applications, comprising the synthesis, characterization, and analysis of thermal sensing performance using PL emissions in the BWs of Y3Al5O12 (YAG), Y2O3, and Y4Al2O9 (YAM) co-doped with Nd3+ and Yb3+. The first two host matrices were synthesized via the modified Pechini method for co-doping engineering to optimize the concentrations of Nd3+ and Yb3+ for ideal PL emission. To obtain well-dispersed individual nanocrystals (NCs), YAG: Nd3+- Yb3+ and Y2O3: Nd3+-Yb3+ were synthesized by the solvothermal route and the two-step urea-based route, respectively, with conditions systematically optimized to fulfill the requirements of this thesis. The third host matrix, YAM, was also studied using the modified Pechini synthesis to investigate its thermal response when single-doped with Nd3+ and co-doped with Nd3+ and Yb3+. Lastly, a new synthesis method for YAM was explored. The findings showed that YAG: Nd3+-Yb3+ exhibited great potential, particularly after applying a silica coating around the NCs synthesized by the solvothermal route. This coating allowed annealing at 850°C to enhance the PL emission without agglomerating the NCs. The resulting YAG: Nd3+-Yb3+@SiO2 nanoparticles (NPs) had a final size of 87 ± 20 nm, a relative thermal sensitivity (Sr) of 0.60%.K-1, and thermal resolution (δT) of 0.2 K at physiological temperature. Y2O3: Nd3+-Yb3+ NCs of 22 ± 10 nm had Sr of ~ 0.50%.K-1, but δT ~ 0.4 K due to a lower signal-to-noise ratio. YAM, when single-doped with Nd3+, revealed competitive thermal response with Sr = 0.50%.K-1 and δT = 0.3 K at body temperature. However, co-doping YAM with both Nd3+ and Yb3+ ions hampers the thermal sensing efficiency to less than 0.40%.K-1 of Sr at physiological temperature, with δT fluctuating between 0.2 and 0.7 K across the temperature range. Thus, this study paves the way for improving the synthesis and applications of the oxides in nanothermometry and highlights promising prospects of Nd3+-Yb3+ co-doped YAG nanothermometers thanks to their decreased size, good thermal sensing features, and intense PL emission within the BWs.